Children With Reduced Cognitive Efficiency and Addition of Natural Numbers up to 20: A Case Study - Budínová, Irena; Janík, Tomáš (Revija za elementarno izobraževanje, 2021)
The study deals with teaching and learning the addition of natural numbers up to 20 in the first two years of primary school. The first part presents the theoretical background for addition of natural numbers, the procedural and conceptual approach to addition, and the theory of the additive triad. The causes of the difficulties some children have with the field of the addition of natural numbers are outlined, and the issue of reduced cognitive efficiency is briefly introduced as one of the causes. The second part of the study presents a case study of a girl (7 years old) who experienced difficulty in learning addition. The approaches to and results of remedial tutoring completed by the girl are described. In the discussion, the issue of the addition of natural numbers is incorporated into a broader pedagogical context.
Keywords: learning addition, pupils with learning difficulties in mathematics, cognitive efficiency, natural numbers, additive triad, case study